2017
DOI: 10.1002/cem.2963
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal image analysis in tissue diagnostics for skin melanoma

Abstract: Early diagnosis is a corner stone for a successful treatment of most diseases including melanoma, which cannot be achieved by traditional histopathological inspection. In this respect, multimodal imaging, the combination of TPEF and SHG, features a high diagnostic potential as an alternative approach.Multimodal imaging generates molecular contrast, but to use this technique in clinical practice, the optical signals must be translated into diagnostic relevant information. This translation requires automatic ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…250 MPLSM provides high-resolution uorescence imaging, allowing visualization of cellular and subcellular structures of the epidermis and upper dermis. 251,252 MPLSM based morphologic features of skin cancer images are comparable to traditional histopathology. 252 Latest updates on multiphoton scanning for skin cancer diagnosis are summed in Table 13.…”
Section: Multi Photon Scanningmentioning
confidence: 97%
“…250 MPLSM provides high-resolution uorescence imaging, allowing visualization of cellular and subcellular structures of the epidermis and upper dermis. 251,252 MPLSM based morphologic features of skin cancer images are comparable to traditional histopathology. 252 Latest updates on multiphoton scanning for skin cancer diagnosis are summed in Table 13.…”
Section: Multi Photon Scanningmentioning
confidence: 97%
“…9 The analysis of the multispectral Raman data of biological samples requires sophisticated data analysis, no matter if spontaneous or coherent Raman scattering is used. 10,11 This is due to the fact that differences in the concentration of marker molecules like protein, DNA, and lipids are rather small for different tissue types. Therefore, appropriate spectral pre-processing steps to correct for background signals and other illumination artefacts are needed.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…Therefore, appropriate spectral pre-processing steps to correct for background signals and other illumination artefacts are needed. 10,12 In this contribution, we have simultaneously recorded hyperspectral CARS and SRS datasets for head and neck tissue samples, analyzed the datasets by multispectral data analysis approaches, and compared the results.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…In this context, it has been shown that multimodal nonlinear imaging, using different methods such as coherent anti-Stokes Raman scattering (CARS), two-photon excited autofluorescence (TPEF), two-photon excited fluorescence lifetime imaging (2P-FLIM) and second harmonic generation (SHG), is a powerful tool for the label-free characterization of the molecular composition of cells and tissues, enabling the visualization of the distribution of molecular markers with subcellular spatial resolution and the correlation of their function in tissue [15,16,17,18,19]. Using machine learning image processing algorithms, the nonlinear image data can be translated into biomedical information [20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%